2016
DOI: 10.1093/intqhc/mzw083
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring maternal and newborn health outcomes in Bauchi State, Nigeria: an evaluation of a standards-based quality improvement intervention

Abstract: ObjectiveThis study assessed the correlation between compliance with set performance standards and maternal and neonatal deaths in health facilities.DesignBaseline and three annual follow-up assessments were conducted, and each was followed by a quality improvement initiative using the Standards Based Management and Recognition (SBM-R) approach.SettingTwenty-three secondary health facilities of Bauchi state, Nigeria.ParticipantsHealth care workers and maternity unit patients.Main outcome measuresWe examined tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Research around incentives, both financial and non-financial, has yielded mixed results; reviews of conditional cash transfers and similar programs for health care consumers have suggested that individuals can be responsive to small, immediate rewards [34]. The benefit of recognition ceremonies and awards (such as certificates and plaques) to motivate provider behavior is consistent with Jhpiego’s experience implementing quality improvement initiatives through the standards-based management and recognition (SBM-R) approach in 30 countries [35, 36]. After this project ended, the study team organized a dissemination event in each district to present study results to participants and stakeholders, as well as provide recognition in the form of certificates or engraved plaques for high-performing districts, health facilities, district trainers, practice coordinators, and proxies.…”
Section: Discussionmentioning
confidence: 94%
“…Research around incentives, both financial and non-financial, has yielded mixed results; reviews of conditional cash transfers and similar programs for health care consumers have suggested that individuals can be responsive to small, immediate rewards [34]. The benefit of recognition ceremonies and awards (such as certificates and plaques) to motivate provider behavior is consistent with Jhpiego’s experience implementing quality improvement initiatives through the standards-based management and recognition (SBM-R) approach in 30 countries [35, 36]. After this project ended, the study team organized a dissemination event in each district to present study results to participants and stakeholders, as well as provide recognition in the form of certificates or engraved plaques for high-performing districts, health facilities, district trainers, practice coordinators, and proxies.…”
Section: Discussionmentioning
confidence: 94%
“…Improved care in the 22 HFs was similar to the effects seen in other regions of Tanzania, as well as in Ethiopia and Nigeria, where the SBM-R tool is widely used. [21][22][23] Third, data improvement efforts were an embedded part of the intervention, as recommended by effective large-scale maternal health programmes in Africa. 36 37 In particular, in synergy with the SBM-R approach, facilitybased analysis and utilisation of perinatal audit data in quality improvement meetings appeared central to understand the opportunities to avoid adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The Standards-Based Management and Recognition approach (SBM-R), a validated performance and quality improvement method, developed by Jhpiego, was implemented collaboratively. [21][22][23] SBM-R quality assessments in each facility were conducted by a team led by the regional nursing officer and consisting of representatives from the regional and municipal health offices, the HFs and CCBRT. Assessors spent 2-3 days in each facility performing direct observations and scoring (expressed in percentages) using the SBM-R tool and provided immediate feedback to the HFs.…”
Section: Standards-based Quality Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…The MPDSR Assessment report for 2016 put the maternal mortality ratio at 575, with a total T health facilities put at 1034 across Bauchi State. Kabo et al, (2016) in their study entitled Monitoring Maternal and New born Health Outcome in Bauchi State, found out that institutional neonatal mortality rate in Bauchi decreased from 9 to 2 deaths per 1000 live births, while the institutional maternal mortality ratio dropped from 4113 to 1317 deaths per 100 000 live births. The problem of maternal mortality reflects the low social status of women in the state.…”
Section: Statement Of the Research Problemmentioning
confidence: 99%